Fractional Burgers Fluid Flow Due to Metachronal Ciliary Motion in an Inclined Tube - Mann, Amer Bilal; Shaheen, Sidra; Maqbool, Khadija; Poncet, Sébastien (Frontiers in Physiology, 2019)
Cilia-induced flow of fractional Burgers fluid is studied in an inclined tube for both symplectic and antiplectic wave patterns. The solution of the problem is persued under the long wave length limitation. The fractional Adomian decomposition method is employed to evaluate the pressure gradient. Mathematical expressions for the axial velocity, frictional force, pressure gradient and stream function are obtained and the influence of the main operating parameters is discussed in detail. It is noted that the velocity profile is more dominant in the case of antiplectic waves compared to symplectic ones, which confirms former results obtained with more complex numerical solvers.